2021
DOI: 10.1021/acs.organomet.1c00499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pincer Methylation on the Selectivity and Activity in (PNP)Cobalt-Catalyzed C(sp2)–H Borylation

Abstract: Cobalt complexes supported by a tetramethylated PNP pincer ligand (Me 4 iPr PNP = 2,6-( i Pr 2 PCMe 2 ) 2 (C 5 H 3 N)) have been synthesized and structurally characterized. Examples include cobalt(I)−choride, −methyl, −aryl, and −benzofuranyl derivatives. The performance of these compounds was evaluated in the catalytic borylation of fluorinated arenes using B 2 Pin 2 as the boron source. While P−C bond cleavage, a known deactivation pathway in [(PNP)Co]-catalyzed borylation, was suppressed, the overall activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…194 A similar effect of the fluorine atom has been observed in the reactions mediated by the cobalt(III)-trihydride 37. 195 A detailed mechanistic study, including stoichiometric isotopic experiments and the kinetic analysis of all main elemental steps of the catalysis, strongly support the two cycles defined by the trihydride 104 and the hydride-boryl derivatives IrH 2 (Bpin){k 3 pinBH to give H 2 and complexes 111 and 112 in a sequential manner. Compound 112 activates a C-H bond of two molecules of arene to form the functionalized arene and regenerate 111 and 104, also in a sequential manner.…”
Section: Borylation Of Arenesmentioning
confidence: 78%
See 1 more Smart Citation
“…194 A similar effect of the fluorine atom has been observed in the reactions mediated by the cobalt(III)-trihydride 37. 195 A detailed mechanistic study, including stoichiometric isotopic experiments and the kinetic analysis of all main elemental steps of the catalysis, strongly support the two cycles defined by the trihydride 104 and the hydride-boryl derivatives IrH 2 (Bpin){k 3 pinBH to give H 2 and complexes 111 and 112 in a sequential manner. Compound 112 activates a C-H bond of two molecules of arene to form the functionalized arene and regenerate 111 and 104, also in a sequential manner.…”
Section: Borylation Of Arenesmentioning
confidence: 78%
“…194 A similar effect of the fluorine atom has been observed in the reactions mediated by the cobalt( iii )-trihydride 37 . 195…”
Section: Reactions Of C–h Functionalization Based On Sequential σ-Bon...mentioning
confidence: 99%
“…Structures, features, steric maps, and percent buried volumes (% V bur ) , of (A) ( iPr PNP)­Co­(CH 2 SiMe 3 ), (B) (Me 4 iPr PNP)­Co­(CH 2 SiMe 3 ), and (C) 1-CH 2 SiMe 3 . The Co atom defines the center of the xyz coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…These observations established that borylation activity with 6-CH 2 SiMe 3 trends in the order meta (to fluorine) > para > ortho . Additional substrate exploration demonstrated that borylations using 6-CH 2 SiMe 3 suffered from many of the same functional group incompatibilities as those catalyzed by ( iPr PNP)­Co­(H) 2 BPin (see the Supporting Information for complete details), as nitriles, chlorides, bromides, and iodides were not tolerated …”
Section: Resultsmentioning
confidence: 99%
“…Cobalt-catalyzed borylation methods have been discovered that offer regioselective chemistry distinct from iridium catalysts . Use of bis­(phosphino)­pyridine (PNP) pincers produced catalysts with high ortho to fluorine selectivity including examples that are functionalized indiscriminately by iridium catalysts to yield statistical mixtures of products. , Mechanistic studies established that the ortho to fluorine selectivity arises from rapid C­(sp 2 )–H oxidative addition to the cobalt­(I) pincer that generates cobalt­(I)-aryl intermediates arising from a thermodynamically controlled “ortho-to-fluorine” effect .…”
Section: Introductionmentioning
confidence: 99%